Analysis of the coefficient of friction at the workpiece-tool interface in milling of high strength compacted graphite cast irons - da Silva L.R.R. (2019)
© 2019 Elsevier B.V.The coefficient of friction at the workpiece-tool interface is one of the main influencing parameters in machining. It can be tribologically investigated using conventional and open tribometers, however, there is no consensus as to which type of test has the best correlation with the real machining process. This work aims at investigating the use of three different methods to measure the coefficient of friction in the machining of three types of high strength compacted graphite cast irons, with variations in the size of the free graphite phase and the presence or absence of molybdenum carbides in the matrix. The coefficient of friction of the process was measured using two progressive load conventional tribological tests, the progressive load single sliding test with load ranging from 0.5 to 40 N and the progressive load reciprocate sliding test in both dry and starved lubrication regimen, with load ranging from 48 to 83 N. The coefficient of friction was also measured in a conventional machining center used as an open tribometer, where ramp milling tests were performed in workpieces fixed on a piezoelectric dynamometer, with a cutting depth varying from 100 µm to 0, to simulate a regressive load. The following machining parameters were varied: cutting speed, feed rate, tool geometry, tool coating and the use of minimum quantity of lubrication in contrast to dry machining. As the main results, the predominance of lubrication, even in small quantities, was observed as the most influential parameter in the coefficient of friction. An inverse relationship was also observed between the hardness of the materials and the coefficient of friction independent of the lubrication condition used. The results of the coefficient of friction obtained in progressive load reciprocate sliding and open tribometer tests showed the best correlation with those found in the literature for this kind of materials.